English as a Global Language in Islamic Education: Students' Perceptions and Religious Identity - Marwa Marwa; Nurul Hasanah; Zulfah Fakhruddin; Yessicka Noviasmy (e-Journal of ELTS (English Language Teaching Society), 2026)
English has become an important global language used in international communication, education, and professional development. In Islamic educational contexts, English learning may involve negotiation between global communication needs and the preservation of religious identity. This study aimed to investigate students’ perceptions of English as a Global Language and its compatibility with religious identity in an Islamic senior high school context. This study employed a quantitative descriptive research design involving 40 students of MAN 2 Parepare, Indonesia. The data were collected through a structured questionnaire consisting of 21 items measured using a five-point Likert scale and analyzed using descriptive statistics, including mean scores and standard deviation. The findings revealed that students generally had positive perceptions toward English as a Global Language, with an overall mean score of 4.09 categorized as high. Students strongly recognized the importance of English for global communication, academic purposes, and future career opportunities, although acceptance of different English varieties received a relatively lower score. The findings also showed that students generally perceived English learning as compatible with their religious identity, with an overall mean score of 4.15 categorized as high. Students believed that English learning did not conflict with Islamic values and could coexist with their religious and cultural identities. The study concludes that students in Islamic educational contexts are able to maintain strong religious identities while simultaneously developing positive attitudes toward English as a Global Language. These findings highlight the importance of culturally and religiously responsive English language teaching practices in Islamic educational institutions